Abstract Number ‐ 114: Deep Cerebral Venous Thrombosis requiring Venous Thrombectomy and Intra‐arterial Thrombolysis in Young Pregnant Female - Aakashi Shah; Norman Ajiboye (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Cerebral venous sinus thrombosis (CVST) is a rare cause of stroke and mortality especially in young women and children (1). Even though, first‐line treatment remains anticoagulation, some patients deteriorate and endovascular treatment is needed. Currently there are no randomized controlled trials comparing the efficacy and safety of intracranial thrombolysis and mechanical thrombectomy to standard‐of‐care anticoagulation therapy (2). We present a case of a pregnant lady with CVST with successful clinical outcomes with venous thrombectomy and intraarterial thrombolysis. Methods Case Report Results 30 year old lady with no past medical history, 7 weeks and 4 days pregnant presented with acute progressive encephalopathy associated with nausea, vomiting and headaches. On admission, she was stuporous, had dysarthria, severe hemiparesis, and hemineglect on the right side. She had COVID‐19 infection and her fetus had subchorionic hematoma by ultrasound. Initial CT brain showed extensive cerebral venous sinus thrombosis (CVST). She was intubated and MRI showed venous infarcts. MR venography revealed acute extensive CVST of superior sagittal sinus, vein of galen, right transverse sinus, right sigmoid sinus, and right jugular vein. IV Heparin drip was initiated. Her follow‐up neurological exam deteriorated despite maximal medical therapy. The decision was made for endovascular recanalization. The cerebral angiogram confirmed the occlusion of deep venous system. Thrombectomy of bilateral internal jugular vein and sigmoid sinus was performed with retrieval of thrombi. Post‐thrombectomy runs demonstrated persistent extensive CVST and decision was made for intra‐arterial thrombolysis. A diagnostic catheter was secured in the right internal carotid artery catheter (ICA). Thombolysis was performed with 4 mg/hr recombinant tissue‐plasminogen activator (rt‐PA). Heparin drip IV was continued. Subsequently, the repeat CT brain showed significant improvement in the CVST and interval development of intraparenchymal hemorrhages and subarachnoid hemorrhages. Heparin and rt‐PA were held. The patient was found to have Factor V Leiden mutation and she was started on Enoxaparin 1mg/kg throughout her pregnancy and 6 weeks postpartum. Clinically she demonstrated significant neurologic improvement and was discharged to home from rehabilitation center. Currently, she is thirty‐ four weeks pregnant and neurologically intact without any deficits. Conclusions Pharmacological and mechanical endovascular interventions can have significantly successful clinical outcomes in deep cerebral venous thrombosis. Controlled studies are required to assess the safety and efficacy of these interventions when compared to standard systemic anticoagulation.